(untitled) (Medical Forum Monthly, 2020)
Objective: To determine the distribution of early neonatal morbidities in late preterm infants. Study Design: Descriptive study Place and Duration of Study: This study was conducted at the department of Pediatrics and Neonatology Ayub teaching hospital, Abbottabad from May 2018 to December 2019. Materials and Methods: After taking approval from ethical committee, data was collected from all neonates admitted to department of neonatology, who were born late preterm with gestation of less than 37 weeks but with 34 completed weeks. Total 147 neonates were included in this study. In all neonates who were included in this study, morbidities were evaluated from birth till 7th day of life through clinical examination and relevant investigations and were recorded on proforma. Results: Mean neonatal age was 4 days with SD ± 3.74. Fifty-six percent neonates were male and 44% neonates were female. More over 25% neonates had hyperbilirubinemia, 28% neonates had sepsis, 20% neonates had intrauterine growth restriction, 4% neonates had transient tachypnea of newborn, 15% neonates had hypoglycemia, 16% neonates had respiratory distress syndromes and 13% neonates had apnea. Conclusion: Our study concludes neonatal morbidities like hyperbilirubinemia, sepsis, intrauterine growth restriction, transient tachypnea of newborn; hypoglycemia, respiratory distress syndromes, and apnea are associated with late preterm births.